IMPROVING THE STUDENTS’ ABILITY IN WRITING REPORT GENRE THROUGH MIND MAPPING AT SMP NEGERI 17 PALEMBANG - Erna Novalinda (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
This research was conducted to improve the IX-5 grade students’ ability in writing report genreby using mind-mapping strategy. The population of this research were the IX-5 students ofSMP Negeri 17 Palembang. The total samples were 43 students. In taking the data, theresearcher used classical approach which was taking in three ways, observation, questionnaireand test. In doing the observation data the researcher was helped by two English teachers toknow the students’ improvement from cycle to cycle. The result of the research showed thatthere is good impact to the students’ achievement and ability in writing report genre throughmind-mapping technique. In conclusion, mind-mapping technique is a suitable strategy toimprove the students’ ability in writing report genre.